Pengaruh Iklan, Merek, Beauty Influencer terhadap Keputusan Pembelian Generasi Z Kabupaten Tuban - Monica Putri Utami; Lis Setyowati (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
The aim of the study was to analyse the effect of advertising effectiveness, brand preference, and beauty on purchasing decisions for Scarlett Whitening products in Generation Z in Tuban Regency. This type of quantitative research. This study uses primary data and secondary data. The non-probability sampling technique used a purposive sampling technique, using the slovin formula to calculate the sample so that 100 respondents were determined. The results of the research on the t test and F test show that advertising effectiveness, brand preferences, and beauty influencers influence the decision to purchase Scarlett Whitening products in generation z in Tuban Regency. R Square results of 42.3% and 57.7% are influenced by other variables.